Is Foreign Direct Investment (FDI) Caring for Sustainability? - Martins, Rui Vicente (2022)
Business, politics, social and economic policies on the last decades brought us to inevitability of change. Foreign Direct Investment (FDI) plays a key role on this change as it is a tool for International Business Management on a global world. The relation between FDI and sustainability on the Sub-Saharan countries with lower income has not yet been sufficiently studied so our proposal is to bring a few more conclusions to the overall discussion as we intend to understand if FDI effectively affects the so-called Triple Bottom Line (TBL) pillars of sustainability. Also, we intend to analyse the relation between these pillars themselves as well with another variable, Population Growth. With data obtained from the World Bank (WB), regarding 20 countries, gathered between 2010 to 2018, we analysed 34 indicators composing 11 of the United Nations Sustainable Development Goals (SDG´s). After, we group them by the TBL pillars and evaluate the influence of FDI inflows on their scores using panel data models. Also, the influence between the pillars themselves and variable Population Growth was studied. Our results show a strong, positive correlation between the TBL pillars. FDI has no significant influence on the TBL pillars, and population growth positively affects the Social pillar, affecting negatively the Environmental pillar.